Новые и малоизвестные виды веснянок сем. Nemouridae (Plecoptera) с Сахалина и Курильских островов - Жильцова, Л.А. (Вестник зоологии, 1981)
A new for science species, Nemoura parafulva sp. n., and two little known species of the Nemoura genus, N. sachalinensis M a t s . and N. fulva (Sam.), are described. According to the author’s data 56 stonefly species are known from the Kuril Islands and Sakhalin, 39 species of them inhabit Sakhalin, and 38 — the Kuril Islands. One and the same families and genera (except the Pteronarcidae family absent in the Kuril Islands) are represented in the fauna of the Kuril Islands and Sakhalin. As to the number of species the families are arranged in the following order: Nemouridae (17), Capniidae (9), Chloroperlidae (8), Leuctridae (5), Perlodidae (4), Perlidae (3), Taeniopterygidae and Pteronarcidae (one species each). There are a lot of species common for the Kuril Islands and Sakhalin (22 of 56).